Pragmatism and realism - Will, Frederick L.; Westphal, Kenneth R. (New York: London : Rowman & Littlefield Publishers, INC., 1997)
When historians of philosophy turn to the work of distinguished philosopher Frederick L. Will, Pragmatism and Realism will be an important part of the discussion. In this collection of nine essays, Will demonstrates that a social account of human knowledge is consistent with, and ultimately requires, realism. A timely contribution to the current debate, the book culminates in a naturalistic account of the generation, assessment, and revision of cognitive, moral, and social norms. It is written clearly enough for undergraduates, and includes a critical introduction by the editor discussing the bearing of Will's views on current debates among analytic epistemologists, philosophers of science, and moral theorists
Foreword / Alasdair MacIntyre -- 1. Thoughts and Things -- 2. Truth and Correspondence -- 3. The Concern About Truth -- 4. The Rational Governance of Practice -- 5. Reason, Social Practice, and Scientific Realism -- 6. Reason and Tradition -- 7. Rules and Subsumption: Mutative Aspects of Logical Processes -- 8. Pragmatic Rationality -- 9. Philosophic Governance of Norms
Includes bibliographical references (pages 193-199) and index
Keywords: Knowledge, Theory of; Pragmatism; Realism; Truth